Les risques conchylicoles en Baie de Quiberon. Troisième partie : le risque d’hypoxie pour l’huître creuse Crassostrea gigas. Rapport final du projet Risco 2010-2013 ... - Stanisiere, Jean-Yves; Mazurie, Joseph; Bouget, Jean-Francois; Langlade, Aime; Gabellec, Raoul; Retho, Michael; Quinsat, Kevin; Leclerc, Emilie; Cugier, Philippe; Dussauze, Morgan; Menesguen, Alain; Dumas, Franck; et al. (Ifremer, 2013)
The project “Risco”, supported by the “Pôle Mer” and funded by the Regional Council of Brittany, deals with specific risks of mortality of oysters, Crassostrea gigas, cultivated on the bottom, in a subtidal bay of South Brittany : the bay of Quiberon (56, France). Massive mortalities of oysters were reported in summer 2006 in this bay, exclusively located in the deep muddy area with a positive gradient eastward. A validated biogeochemical model was applied in order to simulate the dissolved oxygen over 2000-2006 : it revealed several episodes of hypoxia, more or less intense according to years, but with the same spatial distribution. This approach proved 2006 to be the most hypoxic year since 2000. The hypoxia was due to a rare conjunction of 3 factors : (a) a local upwelling generated by north-west winds, during a neap tide; (b) an abnormal high temperature of coastal waters; (c) probably an intense phytoplankton bloom in summertime. Due to the stratification induced, oxygen consumption near the bottom ... : L’étude « Risco », labellisée par le Pôle Mer et financée par la région Bretagne, a révélé un facteur insoupçonné d’altération des résultats d’élevage ostréicole en baie de Quiberon (France, 56): l’hypoxie. Elle a ainsi fourni une explication convaincante des mortalités anormales observées sur les huîtres adultes l’été 2006. Le modèle biogéochimique appliqué sur la période 2000-2006 a mis en évidence plusieurs épisodes d’hypoxie d’intensité variable selon les années, mais très géolocalisés. Parmi eux, celui de 2006 s’est avéré exceptionnel, tant par son emprise spatiale que par son intensité. L’hypoxie de 2006 résulte de la conjonction rare de plusieurs phénomènes : (a) un upwelling local généré par des vents de nord-ouest en période de morte-eau (b) des eaux côtières anormalement chaudes (c) probablement un fort bloom estival de phytoplancton. Du fait de la stratification induite, la consommation d’oxygène au niveau du fond excède alors son renouvellement. Le secteur profond et envasé, à l’est de la ...